High-performance source of spectrally pure, polarization entangled photon pairs based on hybrid integrated-bulk optics - Meyer-Scott, Evan; Prasannan, Nidhin; Eigner, Christof; Quiring, Viktor; Donohue, John M.; Barkhofen, Sonja; Silberhorn, Christine (Optics Express)

Direction-tunable enhanced emission from a subwavelength metallic double-nanoslit structure - Song, Xiaohong; Wang, Nini; Yan, Ming; Lin, Cheng; Förstner, Jens; Yang, Weifeng (Optics Express)
Controlling light emission out of subwavelength nanoslit/aperture structures is of great important for highly integrated photonic circuits. Here we propose a new method to achieve direction-tunable emission based on a compact metallic microcavity with double nanoslit. Our method combines the principles of Young’s interference and surface plasmon polaritons interference. We show that the direction of the far-field beam can be controlled over a wide range of angles by manipulating the frequency and relative phase of light arriving at the two slits, which holds promise for applications in the ultracompact optoelectronic devices.
Keywords: tet_topic_plasmonics

Manipulation of vector beam polarization with geometric metasurfaces - Guo, Qinghua; Schlickriede, Christian; Wang, Dongyang; Liu, Hongchao; Xiang, Yuanjiang; Zentgraf, Thomas; Zhang, Shuang (Optics Express)

Directional optical switching and transistor functionality using optical parametric oscillation in a spinor polariton fluid - Lewandowski, Przemyslaw; Luk, Samuel M. H.; Chan, Chris K. P.; Leung, P. T.; Kwong, N. H.; Binder, Rolf; Schumacher, Stefan (Optics Express)

Two-dimensional switchable blue phase gratings manufactured by nanosphere lithography - Wahle, Markus; Brassat, Katharina; Ebel, Justus; Bürger, Julius; Lindner, Jörg K. N.; Kitzerow, Heinz-Siegfried (Optics Express)
Keywords: Atomic and Molecular Physics; and Optics

Impact of carbon-ion implantation on the nonlinear optical susceptibility of LiNbO3 - Spychala, Kai J.; Berth, Gerhard; Widhalm, Alex; Rüsing, Michael; Wang, Lei; Sanna, Simone; Zrenner, Artur (OPTICS EXPRESS)
In this work we study the impact of ion implantation on the nonlinear optical properties in MgO:LiNbO3 via confocal second-harmonic microscopy. In detail, we spatially characterize the nonlinear susceptibility in carbon-ion implanted lithium niobate planar waveguides for different implantation energies and fluences, as well as the effect of annealing. In a further step, a computational simulation is used to calculate the implantation range of carbon-ions and the corresponding defect density distribution. A comparison between the simulation and the experimental data indicates that the depth profile of the second-order effective nonlinear coefficient is directly connected to the defect density that is induced by the ion irradiation. Furthermore it can be demonstrated that the annealing treatment partially recovers the second-order optical susceptibility.

Transmitting more than 10 bit with a single photon - Tentrup, Tristan B. H.; Hummel, Thomas; Wolterink, Tom A. W.; Uppu, Ravitej; Mosk, Allard P.; Pinkse, Pepijn W. H. (Optics Express)

Phase sensitive properties and coherent manipulation of a photonic crystal microcavity - Quiring, Wadim; Jonas, Björn; Förstner, Jens; Rai, Ashish K.; Reuter, Dirk; Wieck, Andreas D.; Zrenner, Artur (Optics Express)
We present phase sensitive cavity field measurements on photonic crystal microcavities. The experiments have been performed as autocorrelation measurements with ps double pulse laser excitation for resonant and detuned conditions. Measured E-field autocorrelation functions reveal a very strong detuning dependence of the phase shift between laser and cavity field and of the autocorrelation amplitude of the cavity field. The fully resolved phase information allows for a precise frequency discrimination and hence for a precise measurement of the detuning between laser and cavity. The behavior of the autocorrelation amplitude and phase and their detuning dependence can be fully described by an analytic model. Furthermore, coherent control of the cavity field is demonstrated by tailored laser excitation with phase and amplitude controlled pulses. The experimental proof and verification of the above described phenomena became possible by an electric detection scheme, which employs planar photonic crystal microcavity photo diodes with metallic Schottky contacts in the defect region of the resonator. The applied photo current detection was shown to work also efficiently at room temperature, which make electrically contacted microcavities attractive for real world applications.
Keywords: tet_topic_phc

Discrete plasmonic solitons in graphene-coated nanowire arrays - Kou, Yao; Förstner, Jens (Optics Express)
e study the discrete soliton formation in one- and two- dimensional arrays of nanowires coated with graphene monolayers. Highly confined solitons, including the fundamental and the higher-order modes, are found to be supported by the proposed structure with a low level of power flow. Numerical analysis reveals that, by tuning the input intensity and Fermi energy, the beam diffraction, soliton dimension and propagation loss can be fully controlled in a broad range, indicating potential values of the graphene-based solitons in nonlinear/active nanophotonic systems.
Keywords: tet_topic_plasmonics; tet_topic_polariton

On-chip generation of photon-triplet states - Krapick, Stephan; Brecht, Benjamin; Herrmann, Harald; Quiring, Viktor; Silberhorn, Christine (Optics Express)

Thermochromic modulation of surface plasmon polaritons in vanadium dioxide nanocomposites - Jostmeier, Thorben; Mangold, Moritz; Zimmer, Johannes; Karl, Helmut; Krenner, Hubert J.; Ruppert, Claudia; Betz, Markus (Optics Express)
We propose and implement a new concept for thermochromic plasmonic elements. It is based on vanadium dioxide (VO2) nanocrystals located in the near field of surface plasmon polaritons supported by an otherwise unstructured gold thin film. When the VO2 undergoes the metal-insulator phase transition, the coupling conditions for conversion of light into propagating surface plasmon polaritons change markedly. In particular, we realize thermochromic plasmonic grating couplers with substantial switching contrast as well as tunable plasmonic couplers in a Kretschmann configuration. The use of VO2 nanocrystals permits highly repetitive switching and room temperature operation. Simulations based on the actual dielectric function of our VO2 nanocrystals agree well with the experiment.

Asymmetric band gap shift in electrically addressed blue phase photonic crystal fibers - Wahle, M.; Ebel, J.; Wilkes, D.; Kitzerow, Heinz-Siegfried (Optics Express)
Keywords: Atomic and Molecular Physics; and Optics

Asymmetric band gap shift in electrically addressed blue phase photonic crystal fibers - Wahle, M.; Ebel, J.; Wilkes, D.; Kitzerow, Heinz-Siegfried (Optics Express)
Keywords: Atomic and Molecular Physics; and Optics

Resonant radiation from oscillating higher order solitons - Driben, R.; Yulin, A. V.; Efimov, A. (Optics Express)

Resonant radiation from oscillating higher order solitons - Driben, R.; Yulin, A. V.; Efimov, A. (Optics Express)

Versatile endless optical polarization controller/tracker/demultiplexer - Koch, Benjamin; Noé, Reinhold; Sandel, David; Mirvoda, Vitali (OPTICS EXPRESS)

Liquid crystal assisted optical fibres - Wahle, M.; Kitzerow, Heinz-Siegfried (Optics Express)
Keywords: Atomic and Molecular Physics; and Optics

Real-time coherent detection of phase modulated ultrashort pulses after time-to-space conversion and spatial demultiplexing - Shayovitz, Dror; Herrmann, Harald; Sohler, Wolfgang; Ricken, Raimund; Silberhorn, Christine; Marom, Dan M. (Optics Express)
Keywords: Atomic and Molecular Physics; and Optics

Full-field reconstruction of ultrashort waveforms by time to space conversion interferogram analysis - Shayovitz, Dror; Herrmann, Harald; Sohler, Wolfgang; Ricken, Raimund; Silberhorn, Christine; Marom, Dan M. (Optics Express)
Keywords: Atomic and Molecular Physics; and Optics

An optimized photon pair source for quantum circuits - Harder, Georg; Ansari, Vahid; Brecht, Benjamin; Dirmeier, Thomas; Marquardt, Christoph; Silberhorn, Christine (Optics Express)